Associative and Propositional Processes in Evaluation : Conceptual, Empirical, and Metatheoretical Issues Reply to Albarracin, Hart, and McCulloch (2006), Kruglanski and Dechesne (2006), and Petty and Brinol (2006). [article]. - Gawronski, Bertram
Commentators on B. Gawronski and G. V. Bodenhausen's (2006) recently proposed associative-propositional evaluation (APE) model raised a number of interesting coneptual, empirical, and metatheoretical issues. The authors consider these issues and conclude that (a) the conceptual critisicms raised against the APE model are based on misinterpretations of its basic assumptions, (b) the empirical critisicms are unfounded, as they are inconsistent with the available evidence, and (c) the proposed alternative accounts appear to be less parsimonious and weaker in their predictive power than the APE model. Nevertheless, the commentators offered valuable suggestions for extentions of the APE model, which the authors discuss with respect to their implications for new directions in attitude reaseach. -- (from the author)
Keywords: Attitude change; Cognitive, consistency; Dual-process models; Evaluative conditioning; Implicit measures